Hábito de frutificação, fenologia, adaptabilidade e estabilidade de pereiras para regiões subtropicais - Barbosa, Caio Morais de Alcântara (2017)
In recent years, the cultivation of pear tree (Pyrus sp.) in Brazil had a little expansion, which caused the pear to be the second most imported fruit by the Brazilian market. The main producing region is the southern of the country, but there are already cultivars adapted to subtropical regions, such as the states of São Paulo and Minas Gerais. The production of pears in regions of subtropical and tropical climate still finds establishment problems, requesting studies on the climatic variation and its relation with other intrinsic factors of the different cultivars. The study was conducted at the city of Lavras, Minas Gerais State, Brazil and the objectives were to quantify the fruiting habit determining which type of structure correlates with high levels of productivity; the study the phenological stages; the adaptability and stability, of six cultivars of pear tree ('Shinseiki', 'Packham's Triumph', 'Cascatense', 'Primorosa', 'Seleta' and 'Tenra'), in order to establish strategies for the pruning of pear trees in subtropical regions. For the bearing habit, the following variables were evaluated: percentage of vegetative spurs, reproductive spurs, reproductive brindles, vegetative brindles, and bourses; the num of potentially floriferous buds; and the production per plant. For the phenological study, the duration of the phenological phases in days and the accumulation growing degree-days (GDD) for the main phenological events were studied in two types of structures (reproductive spurs and reproductive brindles). All the evaluations were carried out in two consecutive productive cycles. It was concluded that the cultivars presented different fruiting habits. The percentages of reproductive sprus and bourses are directly related to the greater production, occurring an inverse relation between the percentage of vegetative spurs and reproductive spurs. The pruning of each cultivar should be directed to preserve structures related to higher levels of production. In relation to the phenological study, there was no difference in the total duration in days of the phenological cycle of the cultivars. There was a difference in the beginning of flowering between the cultivars, from one year to the next, due to climatic conditions and pruning times. The accumulation of degrees of development (GDD) showed a variation between the years, in the interval from pruning to the beginning of sprouting, however there was no variation in the interval from pruning to harvesting. ‘Seleta’ and ‘Shinseiki' are the cultivars that present better adaptability and stability for subtropical regions.